Identitas Budaya Melayu di Asahan, Sumatera Utara - Wahyuda, Tri; Nur, Muttaqin; Siregar, Yusra Dewi (Polyscopia, 2024)
This article examines the cultural customs of the Asahan community during the era of the Asahan Kingdom, a historically Malay kingdom with deep Islamic influences located in what is now North Sumatra. Although Malay culture is predominant, the region has also seen the integration of Toba Batak and Javanese communities, enriching its cultural landscape over time. This study aims to analyze the role of Malay culture in shaping Asahan’s identity within the broader context of East Sumatra. Using a qualitative approach that combines literature review and field observations, the research highlights the significant impact of Malay cultural values—especially in religious beliefs, customs, and enduring social practices—on local identity. These findings provide valuable insights into the forms and preservation of Malay cultural heritage in Asahan, emphasizing its relevance in fostering a cohesive community identity.